Balai Penerangan Pemuda Indonesia dalam Narasi Masa Lampau - Zusneli Zubir (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of the study was to reveal the influence and activities in the Indonesian Youth Information Center (BPPI) building during the Dutch Colonial period, and the story of the heroic youth in defending independence. The research method uses historical methods consisting of heuristics, criticism, interpretation, and historiography. The results showed that during the Dutch colonial period, the BPPI building functioned as a gathering place for Vereeniging merchants who did business in the Gadang Market, Mudik Market, Batipuh Market, and Malintang Market. In the early days of independence, this building was turned into the Indonesian Youth Information Center. This is where the red and white flag was raised for the first time, the inauguration of the first resident, the formation of the BKR, and the formation of the KNI of West Sumatra. The conclusion of the research in 2017, the Padang City Government started a plan to revitalize the building which will function as a Joang Building museum which will later be equipped with photographs, a map of the old Padang city, a map of the movement of revolutionary youth in defending independence. Keywords: BPPI, Independence, Merchant, Struggle.